Core–shell SiO2@LDHs with tuneable size, composition and morphology. Issue 16 (28th January 2015) - Chen, Chunping; Felton, Ryan; Buffet, Jean-Charles; O'Hare, Dermot
Abstract : We present here a simple method for the synthesis of core–shell SiO2 @LDH (LDH: layered double hydroxide) particles using an in situ co-precipitation method without any pretreatment. Abstract : We present here a simple method for the synthesis of core–shell SiO2 @LDH (LDH: layered double hydroxide) particles using an in situ co-precipitation method without any pretreatment. The LDH composition, the overall particle size and morphology can be tuned giving new opportunities for the development of novel sorbents and catalyst systems.